Solvent-dependent selective "naked eye" chromofluorogenic multifunctional rhodamine-based probe for Al3+, Cu2+, Hg2+, S2− and CN− ions. (26th March 2022) - Podshibyakin, Vitaly А.; Shepelenko, Еvgenii N.; Karlutova, Olga Yu.; Dubonosova, Irina V.; Borodkin, Gennadii S.; Popova, Oksana S.; Zaichenko, Svetlana B.; Dubonosov, Alexander D.; Bren, Vladimir A.; Minkin, Vladimir I.
Abstract: The solvent-dependent selective "naked eye" chromofluorogenic multifunctional rhodamine-based probe 3 for Al 3+, Cu 2+, Hg 2+, S 2− and CN − ions was synthesized and its spectral, luminescent and ionochromic properties were studied. The compound obtained exists in the spirolactam form, confirmed by data of 1 H, COSY, HSQC, HMBC and 13 C NMR spectroscopy. In ethanol, Al 3+ ions selectively, even in the presence of other metal cations (Na +, Ba 2+, Zn 2+, Cd 2+, Ni 2+, Co 2+, Cu 2+, Hg 2+ and Fe 3+ ) initiate the opening of the spirolactam ring, accompanied by the appearance of a new absorption band at 556 nm and the "naked eye" effect with a change in the yellow-green color of the solution to orange-pink. At the same time, the initial fluorescence 3 at 539 nm shifts to the longer 579 nm spectral region. The use of acetone as a solvent allows the selective detection of copper(II) cations that turn the yellow color of a solution of 3 to pink-purple ( λ abs 563 nm) due to the formation of the ring-open complex 3 . Cu 2+ that exhibits emission at 580 nm. Selective detection of Hg 2+ in acetonitrile results in the "naked eye" effect characterized by a change in the color of the solution from bright yellow to pink-cherry ( λ abs 564 nm). The fluorescence of the mercury(II) complex is observed at 587 nm. Complexes 3 . Cu 2+ and 3 . Hg 2+ were used for the sequential selective recognition of S 2− and CN − anions, respectively. A combinatorial molecular logic gate was designed based on the cation/anion sensing ability of probe 3 . Graphical abstract: Image 1 Highlights: The "naked eye" chromofluorogenic multifunctional rhodamine-benzothiazole probe was synthesized. The probe is strongly solvent-dependent, which allows selective detection of Al 3+, Cu 2+ and Hg 2+ . The in situ obtained complexes were used for the sequential selective recognition of S 2− and CN − . A combinatorial molecular logic gate was designed on the basis of the cation/anion sensing ability of the probe.